Analisis Perjanjian Lisensi dalam Perlindungan Hak Kekayaan Intelektual Dalam Perdagangan E-Commerce - Muhammad Rifqi Nur Wachid Adi Pratama; Sodikin (JOURNAL SAINS STUDENT RESEARCH, 2023)
As is known, nowadays, along with the development and progress of technology, all human activities often come into contact with things that are instantaneous. Like trading via e-commerce which is currently popular on various social media and other platforms. This research aims to determine the analysis of licensing agreements in protecting intellectual property rights in e-commerce trading. This research uses normative law using a statutory and conceptual approach. The research results show that the existence of a licensing agreement indirectly represents the granting of rights to the licensing party to use and obtain protection in exercising their economic rights. If there is a process of selling and distributing goods through certain accounts on e-commerce sites by parties who are not authorized to own the license using a certain brand, this action is considered a form of brand infringement. Parties who feel disadvantaged by these actions, as copyright holders of their trademarks, can file a lawsuit for trademark infringement and copyright infringement.